Perilaku Kecurangan Akademik Mahasiswa: Dimensi Fraud Diamond dan Gone Theory - Nita Andriyani Budiman (Akuntabilitas, 2018)
The purpose of this research is to analyze the influence of fraud diamond and gone theory on student academic cheating behavior. Fraud diamonds tested in this study are pressure, opportunity, rationalization, and ability, while the tested theory is greed, need and disclosure. Respondents of this research are accounting students in Central Java. Primary data used in this study were collected by using questionnaires delivered directly to the respondents. Sampling method using purposive sampling technique with the number of respondents as much as 167. Hypothesis testing is done by Structural Equation Modeling (SEM) technique with AMOS program. The results of this study prove that rationalization, ability, and disclosure have effect on student's academic cheating behavior, while pressure, opportunity, greed, and requirement have no effect on to student's academic cheating behavior.